Saltcedar (Tamarix ramosissima) Invasion Alters Decomposer Fauna and Plant Litter Decomposition in a Temperate Xerophytic Deciduous Forest - Bedano, José Camilo (2014)
Plant invasions may alter the soil system by changing litter quality and quantity, thereby affecting soil community and ecosystem processes. We investigated the effect of Tamarix ramosissima invasion on the decomposer fauna and litter decomposition process, as well as the importance of litter quality in decomposition. Litter decomposition and decomposer communities were evaluated in two monospecific saltcedar forests and two native forests in Argentina, in litterbags containing either local litter (saltcedar or dominant native species) or a control litter. Saltcedar invasion produced an increase in Collembola, Acari, and total mesofauna abundance, regardless of the litter type. Control litter decomposition was higher in the native forest than in the saltcedar forest, showing that increased abundance of decomposer fauna does not necessarily accelerate decomposition processes. Local litter decomposition was not different between forests, suggesting that decomposer fauna of both ecosystems is adapted to efficiently decompose the autochthonous litter. Our results suggest that the introduction of a resource with higher quality than the local one has a negative effect on decomposition in both ecosystems, which is more pronounced in the invaded forest than in the native forest. This finding stresses the low plasticity of saltcedar decomposer community to adapt to short-term environmental changes.